Health risk assessment of heavy metals in selected Ethiopian spices. Issue 5 (May 2021) - Tefera, Molla; Teklewold, Almaz
Abstract: A total of 144 spice samples (ajwain, black cumin, coriander and fenugreek) were collected from three districts. For the determination of heavy metals (Cd, Cr, Cu, Pb and Zn) concentrations and human health risks, the spice samples were digested in a mixture of HNO3 and HClO4 . The highest concentrations of Cr (24.85 ± 1.673 mg/kg) and Cu (32.267 ± 7.355 mg/kg) were investigated in ajwain and Zn (54.13 ± 6.122 mg/kg) in fenugreek. However, lowest concentration of Cr and Cu were detected in fenugreek; and Zn in coriander. Cd and Pb were not detected in all spice samples. A positive correlation was observed among Cr, Cu and Zn in fenugreek; Zn with Cr and Cu in black cumin and Zn with Cu in ajwain and coriander. However, negative correlation was observed Cr with Cu and Zn in ajwain and coriander; Cr with Cu in black cumin. THQ values of Cu, Zn and 75% of Cr in all spices were less than 1. About 66.7% of the HI values of the samples under study were less than 1, indicated that the consumers will not experience potential health risks from the intake of individual metals through spices consumption. Abstract : Heavy metals; Spices; Health risk